2021
DOI: 10.3390/ijms22137198
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam’s Effects on Delayed-Rectifier K+ Current and Intermediate-Conductance Ca2+-Activated K+ Channel in Jurkat T-lymphocytes

Abstract: Midazolam (MDZ) could affect lymphocyte immune functions. However, the influence of MDZ on cell’s K+ currents has never been investigated. Thus, in the present study, the effects of MDZ on Jurkat T lymphocytes were studied using the patch-clamp technique. Results showed that MDZ suppressed the amplitude of delayed-rectifier K+ current (IK(DR)) in concentration-, time-, and state-dependent manners. The IC50 for MDZ-mediated reduction of IK(DR) density was 5.87 μM. Increasing MDZ concentration raised the rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…In the presence of PHB (300 µM), neither FLM nor chlorotoxin could overcome the PHB-mediated inhibition of I K(erg) activated by long-lasting membrane hyperpolarization ( Figure 3 D). The results suggested that PHB-induced inhibition of I K(erg) in these cells is unlinked to its propensity to interact with GABA A receptors, as reported previously in other cell types [ 7 , 9 , 33 , 47 , 48 , 49 , 50 ].…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…In the presence of PHB (300 µM), neither FLM nor chlorotoxin could overcome the PHB-mediated inhibition of I K(erg) activated by long-lasting membrane hyperpolarization ( Figure 3 D). The results suggested that PHB-induced inhibition of I K(erg) in these cells is unlinked to its propensity to interact with GABA A receptors, as reported previously in other cell types [ 7 , 9 , 33 , 47 , 48 , 49 , 50 ].…”
Section: Resultssupporting
confidence: 75%
“…The I K(DR) has been previously revealed to be suppressed by pentobarbital, another barbiturate, as well as to display the resurgent K + tail currents during high PT stimulations [ 50 , 53 ] We additionally explored if the PHB could modify the magnitude of I K(DR) in these cells. In this series of experiments, cells were placed in Ca 2+ -free, Tyrode’s solution, which contained 1 µM TTX and 0.5 mM CdCl 2 , and the recording electrode used was filled up with K + -enriched solution.…”
Section: Resultsmentioning
confidence: 99%
“…The procedure was approved by the Animal Care and Use Committee of the National Cheng Kung University, Taiwan WHOLE-CELL PATCH-CLAMP RECORDINGS The technique and preparation procedures resemble our previous study by Foon et al, and our wording used partly resembled their descriptions. 12 Cells used for experiments were dissociated, and an aliquot of cell suspension was transferred to a recording chamber mounted on the stage of an inverted DM-IL microscope (Leica Microsystems, Wetzlar, Germany). Neonatal rat ventricular myocytes were bathed at room temperature (20-25℃) in normal Tyrode's solution containing 1.8mM CaCl2.…”
Section: Isolation and Culture Of Neonatal Rat Ventricular Myocytesmentioning
confidence: 99%